“Efecto de cuatro dosis de fosfonato de calcio-boro en el cultivo de ají charapita (capsicum frustescens L.) en la localidad de Lamas” - Luna Panduro, Luis Fernando (2014)
The present investigation entitled 11 Effect of tour doses of calcium phosphonate - Boro cultivation charapita pepper ( Capsicum frutescens L. ) , in the province of San Martin Lamas 11 aimed to determine the most effective dose of calcium phosphonate - Boro in the development and performance of the pepper crop charapita and perform economic analysis of the treatments under study , for which 4 treatments were evaluated: TO (no application) , T1 (0.25 l.ha-1 of calcium phosphonate - Boro), T2 (0.50 l.ha-1 of calcium phosphonate - Boro ) and T3 ( 0.75 l.ha-1 ·of calcium phosphonate - Boro ) T4 ( 1.0 l.ha-1 of calcium phosphonate - Boro ) . The parameters evaluated were: plant height, number of flowers per plant, number of fruits per ptant, fruit diameter, fruit length, fruit weight per plant per treatment, t ha -1 yield, and finally made an economic analysis of all treatments studied. The main conclusions were: Treatment T4 (1.00 l.ha-1 of calcium phosphonate - Boro ) was that gave the best values and higher average productivity indicators being those of 2514.0 fruits per plant, 3737, 8 Number of flowers per plant, 0.66 cm fruit diameter , 1.49 cm fruit length and a weight of 0.90 g per fruit harvested respectively ; treatment TO ( No application of magnet -b ) , which was the lowest throw average values , and demonstrate that as the dose of magnet -b was reduced charapita pepper plants also decreased the average values of the indicators productivity and treatment scored higher yield ( 37.18430 t /_ha) , net income ( S/.22.688.58) , and the highest percentage in profitability (70 %) was the T3, followed by T2, T1 and TO obtained yields 33.216.60 t I ha, 24,697,90 t I no 21,554,70 t I ha respectively and hence lower values of net income and rate of return.